Diffuse knowledge and practices for Fashion Education: perspectives from a podcast series (Revista de Ensino em Artes, Moda e Design, 2023)
This paper presents a reflection on Fashion education in relation to the diffuse knowledge of educational practices of clothes sewing, or the university triangle: education, extension and research. It starts with the reports collected from the podcast series specially elaborated and carried out for the purposes of the ´´Arts and Crafts/UDESC´´ Research Project and discusses the relevant highlights for thinking about these practices and this education. The main objective of the paper is to present the perspectives reported by those who were interviewed for the series and discuss the approaches and singularities of those contributions. The methodology used includes non-systematized bibliographic research, audio recording of semi-structured interviews and the analysis of discourses compared with the teaching experience of the authors. The results achieved include the perception of continuities and ruptures in the history of Fashion education by those interviewed professionals and the publication of the podcast series in the audio aggregators for free.
Keywords: Fashion education; Home Economics; Arts and Crafts